Queer subjectivities in hospitality labor. Issue 5 (15th April 2022) - Sharp, Megan; Farrugia, David; Coffey, Julia; Threadgold, Steven; Adkins, Lisa; Gill, Rosalind
Abstract: This paper explores the experiences of queer workers in the service economy with a focus on hospitality labor. Studies of gender, sexuality and service labor approached mainstream service work as a scene of compulsory heterosexuality, while literature on the position of queer workers has tended to approach work in terms of structural inequalities that prevent queer workers from participating in the labor market, and has therefore focused on notions of diversity and inclusion as frameworks for understanding how the heteronormativity of service relationships can be overcome. This paper shifts focus to examine how queer subjectivities are enacted within the disciplinary requirements of service labor, and on the way that workers negotiate and contest their positioning at work. The paper situates the subjectivities and laboring practices of queer workers at the nexus of tensions between heteronormativity and the politics of diversity in service venues, and examines how workers negotiate and contest their positioning at work. We explore the normativities that shape permissible queer embodiment at work and show how biographical experiences specific to queer workers inform their laboring practices. The paper shows that queer workers in mainstream hospitality venues are enrolled into a specific mode of interactive service labor that capitalizes on their queer biographies, requires highly cultivated relational capacities, and repositions work as a site of political intervention.